Weed management in zero tillage of wheat problems and solutions - Chhokar, R. S.; Sharma, R. K.; Gill, S. C.; Singh, G. P. (Indian Farming, 2018)
The zero tillage and seeding into surface retained residue with minimum soil disturbance have combined benefits of yield advantage and cost saving along with broader weed control options. Non-selective herbicide like glyphosate and paraquat can be used before wheat seeding, if weeds are present in no till conditions at the time of seeding. Thus in comparison to conventional system, there are more chemical weed management options in zero tillage which can be explored as pre planting opportunities.Hence, zero tillage wheat technology provides economical and sustainable weed management and wheat production option for long term sustainability of natural resources.